Hints to Travellers, Scientific and General, Vol. 2 : Tenth edition, revised and corrected - Royal Geographical Society (Great Britain); Reeves, Edward Ayearst, 1862-1945 (Salt Lake City, UT : Project Gutenberg, 2022)
"Hints to Travellers, Scientific and General, Vol. 2" by the Royal Geographical Society is a scientific publication likely written in the early 20th century. This volume focuses on practical advice for travelers regarding various scientific fields including meteorology, geology, and natural history, essential for those exploring less charted regions. It aims to equip adventurers with the knowledge needed to document and understand the diverse environments they encounter during their journeys. The opening of this volume thoroughly discusses the importance of meteorological observations for travelers. It outlines the different methods individuals can employ to contribute to meteorology, such as keeping detailed weather records and noting non-instrumental observations like wind direction and cloud types. The author emphasizes the value of systematic and meticulous data collection in enhancing the understanding of atmospheric conditions, especially in uncharted territories. The text serves as both a guide and a call to action for explorers to document their findings in order to contribute to the broader scientific understanding of meteorology. (This is an automatically generated summary.)
Meteorology, photography, geology, industry and commerce, archæology, medical, etc.
Release date is 2022-03-20
Michael Ciesielski and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Topographical surveying; Scientific expeditions -- Handbooks, manuals, etc; Spherical astronomy